The Effects of Conflict Management Style on Organization’s Performance of Abu Dhabi National Oil Company - Al Hamadi, Manea Jasem; Abd Razak, Mohd Ridwan (International Business Education Journal, 2025)
Conflict is an inherent aspect of human interaction and organizational dynamics, often arising from differing perspectives, goals, and interests. Effectively managing these conflicts is crucial for maintaining a harmonious and productive work environment. The objective of this study is to investigate the effects of conflict management styles, namely collaborating, compromising, avoiding, accommodating, and competing, on organizational performance, with a focus on the Abu Dhabi National Oil Company (ADNOC). A cross-sectional approach was employed, collecting 357 usable responses through a self-administered questionnaire (SAQ) distributed to employees at ADNOC. Data were analyzed using the Statistical Package for the Social Sciences (SPSS). The regression analysis revealed five key findings: first, collaborating significantly affects organizational performance; second, compromising significantly affects organizational performance; third, avoiding significantly affects organizational performance; fourth, accommodating significantly affects organizational performance; and fifth, competing significantly affects organizational performance. This study provides empirical evidence on the importance of effectively applying various conflict management styles in addressing organizational conflict. The findings offer significant contributions to practitioners, theoretical development, and research methodology.